Development of Augmented Reality Learning System Based on Kolb's Experimential Learning Model - Rasim Rasim; Seni Siti Inayah; Yudi Ahmad Hambali; Eka Fitrajaya Rahman; Dwi Novia Al Husaeni (Elinvo (Electronics, Informatics, and Vocational Education), 2026)
Students’ learning motivation often decreases when the learning method does not align with their individual learning styles, posing a challenge for effective and meaningful education. Augmented Reality (AR) technology offers an interactive solution to increase student engagement. This study aims to develop an AR-based learning system adapted to Kolb’s learning styles: Diverger, Assimilator, Converger, and Accommodator, to support personalized and enjoyable learning. The system was developed using the ADDIE model and an object-oriented approach. Evaluation involved black box testing and user testing based on the Technology Ac-ceptance Model (TAM). Results showed over 80% of students were satisfied with the application, 75% found learning more interesting, and approximately 70% demonstrated increased active participation. TAM analysis revealed an average score of 80.26 and a positive correlation between perceived ease of use and motivation. The application encourages deeper exploration of material and boosts students’ confidence in facing academ-ic challenges. In conclusion, the developed system effectively supports technology-based personalized learn-ing. Its implication suggests that AR integration in education can enhance learning quality and serve as a foundation for future intelligent systems incorporating artificial intelligence.